Two against Lincoln : Reverdy Johnson and Horatio Seymour : champions of the loyal opposition - Harris, William C. (William Charles), 1933- (University Press of Kansas, 2017)
The book is an account of two influential opponents of Lincoln and the Republicans during the Civil War era, Revardy Johnson, conservative Unionist senator of Maryland, and Horatio Seymour, Democrat governor of New York during the Civil War and presidential candidate in 1868.